Future of lithium industry in Chile and the national lithium strategy: integration of solar evaporation, direct lithium extraction, and controlled reinjection - Norman Toro; Iván Salazar; Eleazar Salinas-Rodríguez; Manuel Saldana; Rossana Sepúlveda; Pía C. Hernández; Felipe M. Galleguillos-Madrid; Jonathan Castillo (Minerals Engineering, 2026)

Genome-wide association studies for antioxidant activity in blueberry - Umanath Sharma; Amrita Ghosh; Lourdes Peña-Castillo; Abir U. Igamberdiev; Samir C. Debnath (Molecular Biology Reports, 2026)

P145 Uterine microbiome in fertile and subfertile Colombian Creole mares - I.C. Vélez; A. Úsuga; I.L. Jaramillo-Delgado; L.M. Rendón-Ramos; C. Ríos-Usuga; O. Gonzalez; Y. Ramayo-Caldas; V. Castillo-Vanegas; M.P. Paredes-Higuera (Journal of Equine Veterinary Science, 2026)

Responses of Liolaemus lizards to environmental heterogeneity: Linking microhabitat selection and thermal ecology in southern Patagonia - Candela Victorel; Mauro I. Bonavita; Martin C. Castillo; Débora L. Moreno Azocar; María G. Perotti; Félix B. Cruz; Oscar A. Stellatelli (Journal of Thermal Biology, 2026)

Lethal and sublethal effects of Alexandrium affine and Alexandrium pseudogonyaulax on juveniles of the Pacific oyster Magallana gigas - Ismavy C. Castillo-Quintana; Ignacio Leyva-Valencia; Christine J. Band-Schmidt; Pedro Cruz-Hernández; María del Carmen Rodríguez Jaramillo; José Luis Ramírez Arce (Harmful Algae, 2026)

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Strengthening biodiversity conservation and One Health through ranger monitoring of wildlife health in protected areas - Diego Montecino‐Latorre; Sarah H. Olson; Emily Denstedt; Luis Guerra; Paulo Colchao‐Claux; Lucy Keatts; Aristide Andrianarimisa; Lovasoa Rabarisoa; Manfredo Martínez; Sophalrachana Kong; Devin Vorn; Zeveyda Jhancy Segura; et al. (Conservation Biology, 2026)
The lack of wildlife health (WH) surveillance systems leaves critical gaps in biodiversity conservation and One Health protection. Integrating rangers patrolling protected areas (PAs) into WH monitoring represents a cost‐effective and scalable opportunity to address these gaps at key human–wildlife interfaces and nature strongholds. For the past 2.5 years, organizations across 4 countries have collaborated to pilot this integration. The approach involved establishing a practical definition of health event for rangers patrolling PAs, developing a referential form tailored for rangers to document these events, training key country actors to identify and record health events on this form, merging this form with local forms used by rangers to record other events of interest observed during their patrols (e.g., illegal logging), and training rangers to identify and document health events with the modified local form. We examined 4 case studies involving dozens of PAs in different countries with different languages and local partners. The recording of health events was supported by the Spatial Monitoring And Reporting Tool, SMART, which provides the modified form for rangers on mobile devices and enabled standardized recording of events. Currently, over 200 rangers across more than 50 PAs have been trained, and more than 1000 health events have been recorded. This provides early evidence that rangers could enhance WH monitoring and strengthen biodiversity conservation, ultimately fostering One Health. This initiative lays important groundwork for overcoming key barriers (e.g., lack of personnel and funding) to establishing functional WH surveillance systems in PAs. Still, specific data infrastructure, human resources, and institutional support are needed. It will be important to evaluate the limitations of ranger‐collected data and align monitoring goals with the capabilities of rangers and data managers. Expansion to additional PAs is planned, alongside efforts to integrate ranger‐collected data into multisectoral One Health frameworks.

Evolution of CO2 concentration in indoor-room environments with different ventilation modes - Alvaro Garcia-Corral; Sebastian Düsing; Honey Dawn C. Alas; Henrik Hof; Volker Ziegler; Pedro L. Garcia-Ybarra; Jose L. Castillo (Building and Environment, 2026)

DNA barcoding of the Philippine tigerperches (Centrarchiformes: Terapontidae) - Raisa Mikaelle G. Castillo; Onaya Abdulmalik-Labe; Reynand Jay C. Canoy; Jonas P. Quilang (Aquatic Sciences, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Life-position succulent Euphorbia L. fossils buried in Pleistocene explosive volcanic deposits from Tenerife, Canary Islands, Spain - M.C. Velasco-Flores; L.M. Sender; C. González-Montelongo; A. Santos; P. Cruzado-Caballero; M.C. Martín-Luis; C. Alfayate; C.A. Góis-Marques; C. Castillo (Review of Palaeobotany and Palynology, 2026)

Ancient and recent soils as indicators of the genesis and evolution of Salada de Chiprana from middle Pleistocene to present (Ebro Basin, NE Spain) - M. Tierra; C. Castañeda; F.J. Gracia; R. Rodríguez-Ochoa; J.R. Olarieta; A. Medialdea; O. Castillo (CATENA, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

The IPBES invasion-management framework supports informed decision-making for managing biological invasions - Chika Egawa; K. V. Sankaran; Andy W. Sheppard; Evangelina Schwindt; Llewellyn C. Foxcroft; Sonia Vanderhoeven; Lora Peacock; Maria L. Castillo; Rafael D. Zenni; Jana Müllerová; Ana Isabel González Martínez; John K. Bukombe; et al. (Biological Invasions, 2026)
The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) Thematic Assessment Report on Invasive Alien Species and Their Control presents a “conceptual diagram of management-invasion continuum”, introducing a versatile framework to support decision-making on the management of biological invasions. Drawing on an extensive synthesis of current knowledge, this IPBES invasion-management framework has been developed to broaden the scope of existing invasion curves—which primarily overlay generic management objectives onto a sigmoid curve depicting the expansion of the affected area over time—and to illustrate the applicability of the concept of effective management at different stages of the biological invasion process. To introduce the IPBES invasion-management framework to a wider audience, this paper explains the features of the framework and defines the invasion-stage-based management approaches and the potential outcomes envisaged therein. Reflecting the currently limited management options for biological invasions in marine and other connected-water systems, unlike in terrestrial and closed-water systems, the IPBES invasion-management framework clearly distinguishes between these two groups of systems. For each, it presents management approaches including three key factors that decision-makers should consider concurrently: management objectives, targets, and actions. This framework supports informed decision-making in the management of biological invasions in all ecosystems.

Community-centered approaches to aquaculture in small-scale fisheries - Liliana Sierra Castillo; Christine Knott; Anastasia C. E. Quintana; Ana K. Spalding; Erendira Aceves-Bueno; Jessica Blythe; Antonella Rivera; Bonnie Basnett (Ambio, 2026)
Aquaculture is the fastest-growing seafood production system globally, offering economic and social opportunities for small-scale fishing communities. Yet, it is often introduced through top-down, technocratic approaches that ignore the social-ecological realities of these communities. Drawing on four case studies from Mexico and Honduras, this study uses a multistage, participatory mixed-methods approach to examine the integration of aquaculture into existing fisheries. We focus on governance, social organization, economic assets, and cultural traditions, key yet understudied dimensions of implementation. Findings reveal that projects overlooking these interactions risk deepening inequities, displacing traditional livelihoods, and weakening community cohesion. Success depends on early economic support, recognition of local traditions and social structures, and the creation of context-specific governance systems. Centering community needs and experiences can help design equitable, place-based aquaculture initiatives that strengthen, rather than disrupt, small-scale fishing livelihoods.

Devonian metavolcanic rocks in the Rio Puelo section, Patagonian Andes of Chile: possible implications for the eastern limit of Chaitenia and the origin of the Liquiñe Ofqui Fault Zone - F. Hervé; C.M. Fanning; P. Quezada; P. Castillo; K. Deckart; R.J. Pankhurst; C.W. Rapela; C. Palape; M. Zúñiga; M. Calderón (Journal of South American Earth Sciences, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Dynamics of coastal picoeukaryote communities in response to oil spill disturbances - B. Glasner; I. Morel-Letelier; E. Osses; C. Galvez-Aracena; P. Ávila-Guerrero; C. Henríquez-Castillo; E. Urrejola-Pulido; C.B. Pareja; A.A. Durán; N. Trefault; R. De la Iglesia (Marine Environmental Research, 2026)

Using front face fluorescence for rapid estimation of furosine concentration in heat treated milk: a kinetic study - C. González-Gallardo; N. Ayala; F. Ali; A. Zamora; J. Saldo; M. Castillo (International Dairy Journal, 2026)

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Sex matters: female black corals experience higher stress under different current velocities - L. Palacios-Castillo; S. Navarro-Mayoral; M. Godefroid; C. García-Herrera; F. Tuya; R. Haroun; F. Otero-Ferrer (Coral Reefs, 2026)
Black coral forests play a vital role in mesophotic and deep-water environments, providing habitat and refuge for numerous organisms. Their presence and distribution are influenced by hydrodynamic conditions. Yet, insight into the effect of current velocity on the survival and overall condition of black corals, and how this may differ between sexes during the reproductive period, is lacking. Here, we investigated how the current velocity affected male and female nubbins of Antipathella wollastoni , throughout a 5-week experiment, under three treatments: no (0 cm s −1 ), low (mean ± SE = 5.3 cm s −1 ± 0.27) and high current (10 cm s −1 ± 0.42). We studied both the nubbin state ( i.e. mortality, tissue necrosis and propagule production) and their physiology ( i.e. total antioxidant capacity, TAC). We found higher tissue necrosis and mortality in the no-current treatment. Responses were significantly sex-conditioned across all treatments. All male nubbins survived the experiment and exhibited minimal tissue necrosis (mean ± SE = 4.72% ± 0.77), whereas 33.3% of female nubbins died and showed significantly higher tissue necrosis (37.05% ± 8.57). Propagule release was up to fourfold higher under high current compared to low, whereas nubbins in the no-current treatment produced almost none, likely due to the rapid onset of necrosis preventing the use of this escape response. The findings emphasize the importance of current velocities to rear black corals under controlled conditions, especially given the increased vulnerability of female nubbins during the reproductive period.

Simultaneous consumption of Liolaemus lizards by the raptor Geranoaetus polyosoma in south-central patagonia - Candela Victorel; Martín C. Castillo; Mauro I. Bonavita; Mauro N. Tammone; Laura M. Casalins; Laura Mangini Mas; Valeria S. Ojeda; Débora L. Moreno Azócar; Marcelo F. Bonino; Félix B. Cruz (acta ethologica, 2026)

Sex-specific nutritional requirements of mating in insects with contrasting mating systems - C. Ruth Archer; Matthew R. Carey; Charles E. Grant; Clarissa House; Amy Molotoks; Enrique del Castillo; Zeya Wagner; John Hunt (Animal Behaviour, 2026)

Arabidopsis trehalose phosphate synthaseII (tpsII) mutants are ABA-hypersensitive during early development while tps7 to tps11 show increased drought susceptibility consistent with anomalous stomatal closure and weak post-stress recovery responses - Daniela J. Bonilla-Córdoba; Andrea C. Ruiz-Castillo; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; Lino Sánchez-Segura; John Délano-Frier (Plant Science, 2026)

Spatio-temporal analysis of record-breaking temperature increments across Spain - Ana C. Cebrián; Jesús Asín; Jorge Castillo-Mateo; Alan E. Gelfand (Stochastic Environmental Research and Risk Assessment, 2026)
The study of record-breaking values is of significant interest in environmental sciences. Studying records implies analyzing both their occurrence and their magnitude. Further, the study of this phenomenon within a spatio-temporal framework is vital for evaluating seasonal behaviors, identifying spatial patterns, and quantifying the effect of climate change on it. With interest in record-breaking temperatures, we specify models for these observations rather than models for the entire daily temperature stream. Models specifically designed for record-breaking events must consider two random components: the occurrence and the magnitude of each record. With primary interest in the magnitudes, we model the magnitude data given the occurrence data, with the goal of making inference about their evolution within a spatio-temporal framework. We employ a set of 40 geo-referenced time series of daily temperatures across peninsular Spain. From these, we extract the series of occurrences and values of record-breaking events during the summer months, June, July, and August, spanning from 1960 to 2021. The results reveal that the behavior of the increments is neither spatially nor temporally homogeneous, and that there is significant dependence on the previous day: the occurrence of a record increases the posterior mean of the next day’s increment by between 0.3 and 0.6 °C. It is also found that the posterior mean of the average increment on a record-breaking day during the decade 2012–2021 is approximately 1 °C inland, increasing to around 2°C in some coastal areas. After 30 years, mean increments stabilize near 1°C with a mild downward trend.

Stock identification of the striped mullet Mugil incilis (Actinopterygii: Mugilidae) using truss network, morphometric relationships, and probabilistic models in three regions of the Colombian Caribbean. - K.E. Carrillo-Castro; P. del Monte-Luna; C. Cardenas-Uribe; y.H. Castillo-Navarro (Fisheries Research, 2026)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Trace metal contamination along an estuarine gradient under increasing anthropogenic pressure: A case study from the Guadalquivir estuary (SW Iberian Peninsula) - I. Donázar-Aramendía; C. Megina; J.M. Miró; J. Martín-Gallardo; J.M. Castillo; J.C. García-Gómez (Marine Pollution Bulletin, 2025)

Philippine functional foods: A new frontier in noncommunicable diseases prevention - Myra O. Villareal; Lotis E. Mopera; Gladys C. Completo; Ruel C. Nacario; Marissa V. Romero; Katherine Ann T. Castillo-Israel; Rona Camille M. Lizardo-Agustin; Marianne Joy G. Laya; Roi Miguel M. Obdosantos; Christel Leo O. Romano; Jocelyn E. Serrano; Samuel C. Bobiles; et al. (Food and Humanity, 2025)

Hardware performance analysis for deep learning-based mistletoe detection in UAV imagery - Carlos Bermejo-Sabbagh; Mauricio G. Orozco-del-Castillo; Juan C. Valdiviezo-Navarro; Pedro A.G. Ortiz-Sánchez; Nora L. Cuevas-Cuevas (Computers and Electronics in Agriculture, 2025)

Onychocolone A produced by the fungus Onychocola sp. targets cancer stem cells and stops pancreatic cancer progression by inhibiting MEK2-dependent cell signaling - Maria C Ramos; Gloria Crespo-Sueiro; Nuria de Pedro; Carmen Griñán-Lisón; Caridad Díaz; Víctor González-Menéndez; Francisco Castillo; Jose R Tormo; Olga Genilloud; Fernando Reyes; Rosario Fernández-Godino (Phytochemistry Letters, 2025)

A recently identified mass-transport deposit stack in the Guaymas Basin, Gulf of California (México), and its implication in the basin tectonics - A. Piña; J. Stock; D. Lizarralde; S. Hart; K. Marsaglia; C. Gallegos-Castillo; C. Berndt; A. González-Fernández; C. Mortera-Gutiérrez; A. Martín-Barajas (Marine Geology, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Safety and pharmacodynamics of intranasal recombinant human interferon alpha-2b as antiviral prophylaxis: A phase I-II clinical trial (OLIVO study) - Francisco Hernández-Bernal; Dania Vázquez-Blomquist; Joel M. Quintana-Guerra; Lídice Josué-Díaz; Klaudia Urrutia-Pérez; Karen Urrutia-Pérez; José L. Rodríguez-Reinoso; Jorge C. Castillo-Miranda; Maritza Pacheco-Rodríguez; Iris Valdés-Prado; Marel Alonso-Valdés; Hugo Nodarse-Cuní; et al. (Next Research, 2025)

Impacts of heat stress under oceanic climate on fertility and reproductive physiology of dairy cows subjected to hormonal synchronization - E. N. Martínez; C. Castillo; L. Avendaño-Reyes; J. Hernández; J. L. Benedito; A. Rico; P. Garcia; R. Muiño (International Journal of Biometeorology, 2025)
Regions with oceanic climates are experiencing unprecedented climatic changes. This study assesses the presence of heat stress in these regions and its impact on reproductive in Holstein cows using the Temperature-Humidity Index (THI), a measure of thermal stress. Data was collected from 159 Holstein cows across experiments. Cows underwent a modified double-ovsynch synchronization protocol, while 96 cows were inseminated based on observed estrous. Cows were examined for body temperature, follicle and uterus examination, and serum progesterone concentrations to evaluate the impact of heat stress. The results of cows pregnancy rate in double-ovsynch synchronized cows were 48.5% and 43.3% in summer and winter seasons, respectively. While the pregnancy rate in non-synchronized cows were 29.5% and 32.7% in summer and winter season, respectively. Elevated THI levels (THI ≥ 72) have adversely effects on reproductive physiology, reduced estrous expression, decreased uterine blood flow, and altered progesterone concentrations. Mild heat stress during summer months in oceanic climate negatively impacted reproductive efficiency in dairy cows, for adaptive management strategies. The double-ovsynch protocol effectively stabilized fertility across seasons, demonstrating its value in improving reproductive outcomes under varying thermal conditions.

Different reproductive strategies influence in vitro germination in Chloraea gavilu and Chloraea crispa (Orchidaceae) - G. Pereira; D. Castillo-Novales; O. Jeldes-Cajas; J. T. Otero; C. Arriagada; C. Atala (Brazilian Journal of Botany, 2025)

Effectiveness and implications of spatial background restrictions on model performance and predictions: a special reference for Rattus species - Diane Shiela C. Castillo; Motoki Higa (Landscape and Ecological Engineering, 2025)
Controlling background data selection in presence-only models is crucial for addressing sampling biases and enhancing model performance. While numerous studies have evaluated the impact of various background data selection techniques across different taxa, research remains limited on how spatially restricted background areas and employing random and biased distribution methods, influence model performance for Rattus species predictions. These species often present challenging collection conditions and low trap success rates, potentially leading to spatial biases in the occurrence records that may affect the accuracy of model predictions. Thus, this study examined methods to assess model accuracy variability for Rattus species by applying spatial background restrictions within the study area. These restrictions were defined by four main criteria: (1) areas within islands with documented species occurrences, (2) areas within the species’ extent of occurrence according to IUCN range maps, (3) defined road distance, and (4) varying buffer areas around recorded species occurrences. To further assess the effects of spatial background restrictions on model performance, we used two methods to distribute the background sampling points: random and biased (bias file) method. Our findings demonstrated that the selection of spatial background restrictions and the distribution methods for background sampling points play a critical role in influencing model performance and the accuracy of predicted habitat suitability for Rattus species. Our findings highlight that defining a specific spatial restriction, such as restricting background selection to within 5 km of a road, improves model performance. However, overly narrow or restrictive buffer sizes, such as the 20 km buffer size used in this study, fail to capture the full environmental variability of the species, which can diminish model accuracy. Furthermore, the method used to distribute background sampling points whether random or biased affects species predictive outcomes. To ensure reliable predictions, we recommend a systematic evaluation of different spatial restriction methods and distribution approaches, along with a thorough analysis of their impacts on model performance. This approach not only reveals how outcomes vary across different modeling scenarios but also provides a strong basis for determining the most reliable predictions. By carefully assessing these factors, researchers can refine and optimize habitat suitability models for Rattus species, ultimately enhancing predictive accuracy and ensuring more consistent and dependable results.

Unraveling spatio-temporal patterns of taxonomic, functional, and phylogenetic β-diversity of temperate ant communities after habitat simplification - G. Pérez-Toledo; M. Cuautle; C. Castillo-Guevara; J. G. Miguelena (Biodiversity and Conservation, 2025)

The tps5, tps10 and tps11 class II trehalose phosphate synthase mutants alter carbon allocation to starch and organic and amino acids at two different photoperiods in Arabidopsis - Andrea C. Ruiz-Castillo; Daniela J. Bonilla-Córdoba; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; John Délano-Frier (Planta, 2025)
Main conclusion Altered C and N allocation in response to short- and long photoperiods in class II TPS mutants suggest that they negatively regulate the TPS1-Tre6P metabolic regulator system in A. thaliana . Abstract The biological function of class II TPS genes remains largely enigmatic, although there is evidence that they may play an important regulatory role in plant stress responses as well as in development and growth. Recent findings indicated that part of biological function of TPSII proteins may be related to their capacity to associate with the SnRK1 regulator of metabolism in order to inhibit its nuclear activity. The results of the present study show that insertional mutants of the TPS5 , TPS10 and TPS11 class II TPS genes had a marked effect on the carbon allocation to non-structural carbohydrates, notably starch, and to organic and amino acids during both short- and long-day photoperiods. The results obtained in this study, which resembled those obtained previously in AhTPS1 overexpressing plants, suggest that these particular TPSII proteins may negatively regulate of C and N allocation to non-structural carbohydrates, organic and amino acids mediated by the TPS1-Tre6P central metabolic regulator system in A. thaliana plants. The effect observed was sometimes dependent on of the photoperiod employed and the mutant examined. The mechanism by means of which these TPS II proteins may specifically target TPSI activity and Tre6P levels in order to regulate C and N allocation in A. thaliana in response to short- and long-day photoperiods remains to be determined.

Comparative study of the physicochemical properties of metal organic frameworks in the adsorption of textile dyes - A. N. Pérez-Jasso; I. A. Aguayo-Villarreal; C. K. Rojas-Mayorga; R. Muñiz-Valencia; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Growth characteristics and drought vulnerability of southwest German spruce and pine - Philipp Römer; Edurne Martínez del Castillo; Frederick Reinig; Max C. A. Torbenson; Oliver Konter; Lara Klippel; Ulf Büntgen; Jan Esper (European Journal of Forest Research, 2025)

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Latitudinal propagation and solar wind drivers of Pc5 pulsations during the June 2015 geomagnetic storm - J. A. Lazzús; I. Salfate; M. N. Castillo; J. Lorca-Castillo; C. Olivares-Salazar; A. Rivera-Zepeda (Acta Geodaetica et Geophysica, 2025)

Effect of pH, temperature and adsorbent mass on Cr (VI) adsorption in residues from a coal washing plant - Aime J. Garcia-Lugo; Jorge C. Ríos-Hurtado; Gloria I. Dávila-Pulido; Adrián A. González-Ibarra; Fatima P. Lara-Castillo; Sergio E. Flores-Villaseñor (Environmental Geochemistry and Health, 2025)

Seasonal evolution of the ionospheric summer evening and Weddell Sea Anomalies: Antarctic Peninsula area - M.A. Bravo; C.U. Villalobos; C. Castillo Rivera; A.J. Foppiano; E.M. Ovalle (Advances in Space Research, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Discovering Hidden Archaeal and Bacterial Lipid Producers in a Euxinic Marine System - Dina Castillo Boukhchtaber; F. A. Bastiaan von Meijenfeldt; Diana X. Sahonero Canavesi; Denise Dorhout; Nicole J. Bale; Ellen C. Hopmans; Laura Villanueva (Environmental Microbiology, 2025)
Bacterial membrane lipids are typically characterised by fatty acid bilayers linked through ester bonds, whereas those of Archaea are characterised by ether‐linked isoprenoids forming bilayers or monolayers of membrane‐spanning lipids known as isoprenoidal glycerol dialkyl glycerol tetraethers (isoGDGTs). However, this understanding has been reconsidered with the identification of branched GDGTs (brGDGTs), which are membrane‐spanning ether‐bound branched alkyl fatty acids of bacterial origin, though their producers are often unidentified. The limited availability of microbial cultures constrains the understanding of the biological sources of these membrane lipids, thus limiting their use as biomarkers. To address this issue, we identified membrane lipids in the Black Sea using high‐resolution accurate mass/mass spectrometry and inferred their potential producers by targeting lipid biosynthetic pathways encoded on the metagenome, in metagenome‐assembled genomes and unbinned scaffolds. We also identified brGDGTs and highly branched GDGTs in the suboxic and euxinic waters, potentially attributed to Planctomycetota, Cloacimonadota, Desulfobacterota, Chloroflexota, Actinobacteria and Myxococcota—based on their lipid biosynthetic genomic potential. These findings introduce new possibilities for using specific brGDGTs as biomarkers of anoxic conditions in marine environments and highlight the role of these membrane lipids in microbial adaptation.

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Cadmium availability in rhizosphere and non-rhizosphere soils in cacao farms in Santander, Colombia - C. A. Adarme-Duran; J. Ágreda; P. F. B. Brandão; E. Castillo (Environmental Monitoring and Assessment, 2024)
Current research has highlighted the need to understand the factors influencing cadmium (Cd) availability in cacao-growing soils to elucidate its presence in cacao beans (the raw material for chocolate). Although literature about this topic is increasing, few report the importance of rhizosphere soils on Cd dynamics. This study aimed to understand the changes in available Cd and its association with soil properties (pH, pseudo-total Cd, available Cd (Cd-DTPA), Ca, Mg, K, Na, soil organic carbon, P, Zn, urease activity, exchangeable acidity, and cation exchange capacity) considering rhizosphere and non-rhizosphere soils. Both soil types (51 samples of each, 102 in total) were collected from two Colombian cacao farms. The medians of pseudo-total Cd (1.86 mg kg −1 ) and Cd-DTPA (0.76 mg kg −1 ) were, respectively, about threefold and fourfold higher in rhizosphere compared to non-rhizosphere soils. Principal component analysis showed a clear distinction between rhizosphere and non-rhizosphere soils based on differences in soil properties, which explained the observed changes in available Cd when comparing both soil types. Soil organic carbon and Zn were important drivers of available Cd in rhizosphere soils. Spatial distribution analysis revealed a tendency of available Cd to cluster in rhizosphere soils, and indicated hotspots within each farm. These findings highlight the importance of rhizosphere soils for Cd diagnosis and monitoring, and for improving knowledge about Cd dynamics in the soil- Theobroma cacao L. system.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

The Early Carboniferous age of the Arrayán Formation in the Choapa Accretionary Complex: Implications for its fossil floral content, tectonic setting and evolution of the southwestern Gondwana margin (north-central Chile) - Reynaldo Charrier; Francisco Hervé; Marcia Muñoz-Gómez; C. Mark Fanning; Philippe Moisan; Sofía Rebolledo; Macarena Rojas del Castillo (Journal of South American Earth Sciences, 2024)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Impact of coagulation characteristics on the aggregation of microplastics in upper-ocean turbulence - F. Pizzi; M. Rahmani; C. Romera-Castillo; F. Peters; J. Grau; F. Capuano; L. Jofre (Advances in Water Resources, 2024)

Contrasting Future Growth of Norway Spruce and Scots Pine Forests Under Warming Climate - Edurne Martinez del Castillo; Max C. A. Torbenson; Frederick Reinig; Ernesto Tejedor; Martín de Luis; Jan Esper (Global Change Biology, 2024)
Forests are essential to climate change mitigation through carbon sequestration, transpiration, and turnover. However, the quantification of climate change impacts on forest growth is uncertain and even contradictory in some regions, which is the result of spatially constrained studies. Here, we use an unprecedented network of 1.5 million tree growth records from 493 Picea abies and Pinus sylvestris stands across Europe to predict species‐specific tree growth variability from 1950 to 2016 ( R 2 > 0.82) and develop 21st‐century gridded projections considering different climate change scenarios. The approach demonstrates overall positive effects of warming temperatures leading to 25% projected conifer growth increases under the SPP370 scenario, but these additional carbon gains are spatially inhomogeneous and associated with geographic climate gradients. Maximum gains are projected for pines in Scandinavia, where growth trajectories indicate 50% increases by 2071–2100. Smaller but significant growth reductions are projected in Mediterranean Europe, where conifer growth shrinks by 25% in response to warmer temperatures. Our results reveal potential mitigating effects via forest carbon sequestration increases in response to global warming and stress the importance of effective forest management.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Genetic (co)variation for resistance to white spot syndrome virus, acute hepatopancreatic necrosis, and overall pond survival in Litopenaeus vannamei - Reyes López-Ordaz; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Bruno Gómez-Gil; Sonia A. Soto Rodríguez; Alfonso Martínez Ortega; Juan C. Quintana-Casares; Héctor Castillo-Juárez; Gabriel R. Campos-Montes (Aquaculture International, 2024)

Structure and carbon stocks of accessible mangroves under different conservation status in the Colombian Caribbean - K. Anggi Hapsari; Wilder José Borrero Avellaneda; Barend van Maanen; Juan C. Restrepo; Jaime Polanía; Deysser Jose Sibaja Castillo; Luisa Fernanda Gómez Vargas; J. Alexandra Rodríguez-Rodríguez; Dunia H. Urrego (Forest Ecology and Management, 2024)

Re-evaluating the link between the Ellsworth Mountains and East Antarctica in the Neoproterozoic: Implications for the breakup of Rodinia and the existence of Pannotia - Paula Castillo; Fernando Poblete; Rodrigo Fernández; Joaquín Bastías-Silva; C. Mark Fanning (Precambrian Research, 2024)

Denim washing wastewater treatment by coupling coagulation–flocculation/Fe-garnet filtration: life cycle assessment and the fertilization with the sludge - Y. Robles-Bueno; L. A. Castillo-Suárez; I. Linares-Hernández; V. Martínez-Miranda; L. Garduño-Pineda; C. Alanis; R. Natividad (International Journal of Environmental Science and Technology, 2024)

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

The critical period for yield and grain protein determination in quinoa (Chenopodium quinoa Willd.) - Santiago C. Vásquez; Alejandro del Pozo; Dalma Castillo; Iván Matus; Luz Gómez-Pando; Diego Zamudio-Ayala; Cesar M. Mignone; H. Daniel Bertero; Daniel F. Calderini (Field Crops Research, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Assessing space and time changes in daily maximum temperature in the Ebro basin (Spain) using model‐based statistical tools - Ana C. Cebrián; Jesús Asín; Jorge Castillo‐Mateo; Alan E. Gelfand; Jesús Abaurrea (International Journal of Climatology, 2023)
There is continuing interest in the investigation of change in temperature over space and time. For this analysis, we offer statistical tools to illuminate changes temporally, at desired temporal resolution, and spatially, using data generated from suitable space–time models. The proposed tools can be used with the output from any suitable model fitted to any set of spatially referenced time series data. The tools to assess space and time changes include spatial surfaces of probabilities and spatial extents for events defined by exceeding a threshold. The spatial surfaces capture the spatial variation in the probability or risk of an exceedance event, while the spatial extents capture the expected proportion of incidence of an event for a region of interest. This approach is used analyse the changes in daily maximum temperature in an inland Mediterranean region (NE of Spain) in the period 1956–2015. The area is very heterogeneous in orography and climate, including the central Ebro valley and part of the Pyrenees. We use a collection of daily temperature series obtained from simulation under a Bayesian daily temperature model fitted to 18 stations in that area. The results for the summer period show that, although there is an increasing risk in all the events used to quantify the effects of climate change, it is not spatially homogeneous, with the largest increase arising in the centre of the Ebro valley and the Eastern Pyrenees area. The risk of an increase in the average daily maximum temperature from 1966–1975 to 2006–2015 higher than 1°C is higher than 0.5 over all of the region, and close to 1 in the previous areas. The extent of daily maximum temperature higher than the reference mean has increased 3.5% per decade. The mean of the extent indicates that 95% of the area under study has suffered a positive increment of the average temperature, and almost 70% an increment higher than 1°C.

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

A multi-method approach with machine learning to evaluating the distribution and intensity of prehistoric land use in Eastern Iberia - Wendy Cegielski; Grant Snitker; C. Michael Barton; Joan Bernabeu Aubán; Alfredo Cortell-Nicolau; Salvador Pardo-Gordó; Sean Bergin; Agustín Diez Castillo (Quaternary International, 2023)

Surface activity of protein extracts from seed oil by-products and wettability of developed bioplastics - Seyedeh Fatemeh Mirpoor; Pablo F. Ibáñez-Ibáñez; C. Valeria L. Giosafatto; Teresa del Castillo-Santaella; Miguel A. Rodríguez-Valverde; Julia Maldonado-Valderrama (Food Hydrocolloids, 2023)

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Five-year airborne pollen calendar for a Sonoran Desert city and the relationships with meteorological variability - C. I. Ortega-Rosas; O. G. Gutiérrez-Ruacho; L. Brito-Castillo; M. C. Calderón-Ezquerro; C. Guerrero-Guerra; V. Amaya-García (International Journal of Biometeorology, 2023)

Diet Quality Outcomes of a Cooperative Extension Diabetes Prevention Program - Hannah K. Wilson; Isaura M. Castillo-Hernandez; Ellen M. Evans; Ewan R. Williams; Alison C. Berg (Journal of Nutrition Education and Behavior, 2023)

Salinity effects on the microbiome of a Neotropical water strider - Anakena M. Castillo; Karina A. Chavarria; Kristin Saltonstall; Carlos F. Arias; Luis C. Mejía; Luis F. De León (Hydrobiologia, 2023)

Epiphytes support aquatic consumers of a large floodplain lake ecosystem in the southern Gulf of Mexico - Matteo Cazzanelli; María Mercedes Castillo; Miriam Soria-Barreto; Susana Ochoa-Gaona; Alejandra Sepúlveda-Lozada; Sandra Gisele Patiño-Espinosa; Nelly C. Jiménez-Pérez; Rocío Rodiles-Hernández (Aquatic Sciences, 2023)

Statistical analysis of extreme and record-breaking daily maximum temperatures in peninsular Spain during 1960–2021 - Jorge Castillo-Mateo; Ana C. Cebrián; Jesús Asín (Atmospheric Research, 2023)

Characterization and photocatalytic performance of cement mortars with incorporation of TiO2 and mineral admixtures - Rancés Castillo Lara; Gustavo de Castro Xavier; Maria C. Canela; Juliana Alves Carvalho; Jonas Alexandre; Afonso Rangel Garcez de Azevedo (Environmental Science and Pollution Research, 2023)

Carbon storage in a peri-urban neotropical forest: Assessing its potential and patterns of change over half a century - Griselda Benítez; Laura C. Ruelas-Monjardín; Juan Von Thaden; Israel Acosta-Rosado; Gerardo Alvarado-Castillo; Miguel Equihua (Urban Forestry & Urban Greening, 2023)

Treatment processes and analysis of rainwater quality for human use and consumption regulations, treatment systems and quality of rainwater - C Morales-Figueroa; L A Castillo-Suárez; I Linares-Hernández; V Martínez-Miranda; E A Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

Morphology of buried volcanic bodies in a sedimentary basin of the Pacific Continental Shelf (Gulf of California, Mexico) - Mario González-Escobar; Abril C. Sánchez-Barra; Cristian A. Gallegos-Castillo; Sergio M. Arregui Ojeda; Edgar A. Mastache-Román (Journal of Volcanology and Geothermal Research, 2023)

Prioritization of areas for groundwater monitoring using analytic hierarchy process method in Geographic Information Systems: a case of Mexico - J. M. Esquivel-Martínez; J. L. Expósito-Castillo; M. V. Esteller-Alberich; M. A. Gómez-Albores; C. M. Medina-Rivas; C. R. Fonseca-Ortiz (International Journal of Environmental Science and Technology, 2023)

Sitotroga cerealella-resistant mexican maize races (Zea mays L.), new sources of resistance for commercial maize breeding - Paola Macías-Estrada; Francisco Orozco-González; Gloria Castellanos-Pérez; Adán Castillo-Rosales; Adalberto Ortega-Ortega; Rosa A. Malvar; Daniel Padilla-Chacón; José C. Jiménez-Galindo (Cereal Research Communications, 2023)
Sitotroga cerealella (Oliv.) (Lepidoptera: Gelechiidae) is one of the most important post-harvest pests of maize Zea mays L. Some Mexican maize races ( Z. mays ) could be a novel source of resistance against S. cerealella to improve commercial maize varieties, lines and hybrids. We studied the resistance of Mexican maize races, recollected at Chihuahua State to S. cerealella . We focused on antibiosis and tolerance of maize to S. cerealella . Cristalino-079 maize race shows low level of consumption in grams and percentage, increased larvae mortality before to entering the seed. In addition, Cristalino-079 reduced first adult’s generation and show the largest biological cycle. Due to the small number of emerged adults, there was very little grain weight loss in resistant maize race. The compound that causes high mortality of larvae before to entering the grain is in the pericarp of resistant maize races. The compound that causes longest development time is in the endosperm and embryo. Cristalino-079 show the better level of resistance to S. cerealella infestation in almost all traits studied and this can be used as source of resistance for maize breeding.

Bactericidal activity of silver nanoparticles in drug-resistant bacteria - C. Chapa González; L. I. González García; L. G. Burciaga Jurado; A. Carrillo Castillo (Brazilian Journal of Microbiology, 2023)

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

Mixing methods for solid state electrodes: Techniques, fundamentals, recent advances, and perspectives - Leire Fernandez-Diaz; Julen Castillo; Elene Sasieta-Barrutia; Maria Arnaiz; Marta Cabello; Xabier Judez; Alexandre Terry; Laida Otaegui; Maria C. Morant-Miñana; Aitor Villaverde (Chemical Engineering Journal, 2023)

Community Patterns and Environmental Associations for the Early Life Stages of Fishes in a Highly Transformed Estuary - Gonzalo C. Castillo; Trishelle Tempel; Steven B. Slater; Brian Mahardja; Morgan D. Gilbert (Estuaries and Coasts, 2023)
Estuaries are important fish nursery areas, yet little is known of how environmental forcing influences estuarine fishes during their early life stages. We analyzed environmental and larval-juvenile fish community data in the upper San Francisco Estuary (SFE) from spring to early summer 1995–2017, to better understand drivers of spatiotemporal community patterns in this highly modified estuary. We evaluated community patterns based on the relative abundance and diversity of native and introduced fish in the SFE and their predominant distribution (pelagic, demersal). The upper SFE experienced a downward trend of freshwater outflow and upward trends of temperature and salinity intrusion. Fish relative abundance only showed long-term downtrends for native and introduced pelagic fish groups. The most influential habitat components for relative abundance and diversity of fish groups were in decreasing order: temperature, salinity, Secchi depth, bottom depth, and zooplankton biomass. Early life stages of native and introduced fishes were generally segregated spatially and temporally, with native fishes more associated with cooler, saltier, and higher turbidity habitats during early to mid-spring compared to introduced fishes during late spring to early summer. Community ordination showed that environmental (temperature, salinity, outflow, Secchi depth, and zooplankton biomass) and spatiotemporal factors (month and depth), explained nearly 40% of the total variance. Our results suggest that the shorter duration of planktonic and nektonic stages of demersal fish groups results in higher resiliency compared to pelagic fishes. The declining abundance of pelagic fishes overall seems to be linked to drought effects and human-induced synergistic interactions intensified by climate change.

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

Structure and activity of microbial communities in response to environmental, operational, and design factors in constructed wetlands - M. Verduzo Garibay; A. Fernández del Castillo; J. de Anda; C. Senés-Guerrero; M. S. Gradilla-Hernández (International Journal of Environmental Science and Technology, 2022)

Laurel wilt susceptibility of three avocado (Persea americana Mill.) ecotypes in relation to xylem anatomy, sap flow and leaf gas exchange - Raiza Castillo-Argaez; Aime Vazquez; Joshua L. Konkol; Ana I. Vargas; Randy C. Ploetz; Bruce Schaffer (Trees, 2022)

Spatio-temporal analysis of the extent of an extreme heat event - Ana C. Cebrián; Jesús Asín; Alan E. Gelfand; Erin M. Schliep; Jorge Castillo-Mateo; María A. Beamonte; Jesús Abaurrea (Stochastic Environmental Research and Risk Assessment, 2022)
Evidence of global warming induced from the increasing concentration of greenhouse gases in the atmosphere suggests more frequent warm days and heat waves. The concept of an extreme heat event (EHE), defined locally based on exceedance of a suitable local threshold, enables us to capture the notion of a period of persistent extremely high temperatures. Modeling for extreme heat events is customarily implemented using time series of temperatures collected at a set of locations. Since spatial dependence is anticipated in the occurrence of EHE’s, a joint model for the time series, incorporating spatial dependence is needed. Recent work by Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) develops a space-time model based on a point-referenced collection of temperature time series that enables the prediction of both the incidence and characteristics of EHE’s occurring at any location in a study region. The contribution here is to introduce a formal definition of the notion of the spatial extent of an extreme heat event and then to employ output from the Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) modeling work to illustrate the notion. For a specified region and a given day, the definition takes the form of a block average of indicator functions over the region. Our risk assessment examines extents for the Comunidad Autónoma de Aragón in northeastern Spain. We calculate daily, seasonal and decadal averages of the extents for two subregions in this comunidad. We generalize our definition to capture extents of persistence of extreme heat and make comparisons across decades to reveal evidence of increasing extent over time.

Contrasting Effects of Nitrogen and Labile Carbon Addition on N2O Emissions from Andosols in Costa Rica and Chile Under Controlled Conditions - C. Chinchilla-Soto; M. A. Alfaro; F. Bertsch; A. G. Perez-Castillo (Journal of Soil Science and Plant Nutrition, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Alpinumisoflavone against cancer pro-angiogenic targets: In silico, In vitro, and In ovo evaluation - Honeymae C. Alos; Junie B. Billones; Agnes L. Castillo; Ross D. Vasquez (DARU Journal of Pharmaceutical Sciences, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Correction to: A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

Record tests to detect non-stationarity in the tails with an application to climate change - Ana C. Cebrián; Jorge Castillo-Mateo; Jesús Asín (Stochastic Environmental Research and Risk Assessment, 2022)
The analysis of trends and other non-stationary behaviours at the extremes of a series is an important problem in global warming. This work proposes and compares several statistical tools to analyse that behaviour, using the properties of the occurrence of records in i.i.d. series. The main difficulty of this problem is the scarcity of information in the tails, so it is important to obtain all the possible evidence from the available data. First, different statistics based on upper records are proposed, and the most powerful is selected. Then, using that statistic, several approaches to join the information of four types of records, upper and lower records of forward and backward series, are suggested. It is found that these joint tests are clearly more powerful. The suggested tests are specifically useful in analysing the effect of global warming in the extremes, for example, of daily temperature. They have a high power to detect weak trends and can be widely applied since they are non-parametric. The proposed statistics join the information of M independent series, which is useful given the necessary split of the series to arrange the data. This arrangement solves the usual problems of climate series (seasonality and serial correlation) and provides more series to find evidence. These tools are used to analyse the effect of global warming on the extremes of daily temperature in Madrid.

Population genomic structure of killer whales ( Orcinus orca ) in Australian and New Zealand waters - Isabella M. Reeves; John A. Totterdell; Andrea Barceló; Jonathan Sandoval‐Castillo; Kimberley C. Batley; Karen A. Stockin; Emma L. Betty; David M. Donnelly; Rebecca Wellard; Luciano B. Beheregaray; Luciana M. Möller (Marine Mammal Science, 2022)
Population genomic data sets have enhanced power to detect cryptic and complex population structure and generate valuable information for the conservation and management of wildlife species. Globally, killer whales ( Orcinus orca ) are considered to have a complex population structure due to their ability to specialize in a variety of ecological niches. In the Australasian region, they are found year round in New Zealand waters and are sighted in all Australian waters, with seasonal aggregations in the northwest (NWA) and southwest (SWA). Regionally, there is some knowledge regarding killer whale abundance, diet, acoustics, and social structure, but limited information about their population structure. Here, we present a population structure assessment of Australasian killer whales using 17,491 high quality genome‐wide single nucleotide polymorphisms (SNPs), combined with sequences of the mitochondrial DNA control region. The results indicate a minimum of three populations: New Zealand, NWA, and SWA. These populations present moderate levels of genomic diversity, negligible levels of inbreeding, small effective population sizes, and low contemporary migration rates among them. Mitochondrial DNA analysis elucidated five closely related haplotypes, suggestive of matrilineal societies, consistent with killer whales elsewhere. This information will assist conservation management of killer whales in the Australasian region.

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Whole genomes reveal multiple candidate genes and pathways involved in the immune response of dolphins to a highly infectious virus - Kimberley C. Batley; Jonathan Sandoval‐Castillo; Catherine M. Kemper; Nikki Zanardo; Ikuko Tomo; Luciano B. Beheregaray; Luciana M. Möller (Molecular Ecology, 2021)
Wildlife species are challenged by various infectious diseases that act as important demographic drivers of populations and have become a great conservation concern particularly under growing environmental changes. The new era of whole genome sequencing provides new opportunities and avenues to explore the role of genetic variants in the plasticity of immune responses, particularly in non‐model systems. Cetacean morbillivirus (CeMV) has emerged as a major viral threat to cetacean populations worldwide, contributing to the death of thousands of individuals of multiple dolphin and whale species. To understand the genomic basis of immune responses to CeMV, we generated and analysed whole genomes of 53 Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) exposed to Australia's largest known CeMV‐related mortality event that killed at least 50 dolphins from three different species. The genomic data set consisted of 10,168,981 SNPs anchored onto 23 chromosome‐length scaffolds and 77 short scaffolds. Whole genome analysis indicated that levels of inbreeding in the dolphin population did not influence the outcome of an individual. Allele frequency estimates between survivors and nonsurvivors of the outbreak revealed 15,769 candidate SNPs, of which 689 were annotated to 295 protein coding genes. These included 50 genes with functions related to innate and adaptive immune responses, and cytokine signalling pathways and genes thought to be involved in immune responses to other morbilliviruses. Our study characterised genomic regions and pathways that may contribute to CeMV immune responses in dolphins. This represents a stride towards clarifying the complex interactions of the cetacean immune system and emphasises the value of whole genome data sets in understanding genetic elements that are essential for species conservation, including disease susceptibility and adaptation.

Ecological Drawbacks of Nanomaterials Produced on an Industrial Scale: Collateral Effect on Human and Environmental Health - H. Pérez-Hernández; A. Pérez-Moreno; C. R. Sarabia-Castillo; S. García-Mayagoitia; G. Medina-Pérez; F. López-Valdez; R. G. Campos-Montiel; P. Jayanta-Kumar; F. Fernández-Luqueño (Water, Air, & Soil Pollution, 2021)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Two offshore coral species show greater acclimatization capacity to environmental variation than nearshore counterparts in southern Belize - J. H. Baumann; C. B. Bove; L. Carne; I. Gutierrez; K. D. Castillo (Coral Reefs, 2021)

Exposure duration modulates the response of Caribbean corals to global change stressors - Hannah E. Aichelman; Colleen B. Bove; Karl D. Castillo; Jessica M. Boulton; Alyssa C. Knowlton; Olivia C. Nieves; Justin B. Ries; Sarah W. Davies (Limnology and Oceanography, 2021)
Global change, including rising temperatures and acidification, threatens corals globally. Although bleaching events reveal fine‐scale patterns of resilience, traits enabling persistence under global change remain elusive. We conducted a 95‐d controlled‐laboratory experiment investigating how duration of exposure to warming (~28, 31°C), acidification ( p CO 2 ~ 343 [present day], ~663 [end of century], ~3109 [extreme] μ atm), and their combination influences physiology of reef‐building corals ( Siderastrea siderea , Pseudodiploria strigosa ) from two reef zones on the Belize Mesoamerican Barrier Reef System. Every 30 d, net calcification rate, host protein and carbohydrate, chlorophyll a , and symbiont density were quantified for the same coral individual to characterize acclimation potential under global change. Coral physiologies of the two species were differentially affected by stressors and exposure duration was found to modulate these responses. Siderastrea siderea exhibited resistance to end of century p CO 2 and temperature stress, but calcification was negatively affected by extreme p CO 2 . However, S. siderea calcification rates remained positive after 95 d of extreme p CO 2 conditions, suggesting acclimation. In contrast, P. strigosa was more negatively influenced by elevated temperatures, which reduced most physiological parameters. An exception was nearshore P. strigosa , which maintained calcification rates under elevated temperature, suggesting local adaptation to the warmer environment of their natal reef zone. This work highlights how tracking coral physiology across various exposure durations can capture acclimatory responses to global change stressors.

Two strains of a novel begomovirus encoding Rep proteins with identical β1 strands but different β5 strands are not compatible in replication - Jesús Aarón Avalos-Calleros; Guillermo Pastor-Palacios; Omayra C. Bolaños-Martínez; Armando Mauricio-Castillo; Josefat Gregorio-Jorge; Nadia Martínez-Marrero; Bernardo Bañuelos-Hernández; Jesús Méndez-Lozano; Gerardo Rafael Arguello-Astorga (Archives of Virology, 2021)

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of standardized heavy rainfall profiles for Barcelona city: clustering, rain amounts and intensity peaks - X. Lana; R. Rodríguez-Solà; M. D. Martínez; M. C. Casas-Castillo; C. Serra; A. Burgueño (Theoretical and Applied Climatology, 2020)

Fluoride Exposure Affects Glutamine Uptake in Müller Glia Cells - Ana L. García-López; Jeanett Hernández-Castillo; Luisa C. Hernández-Kelly; Tatiana N. Olivares-Bañuelos; Arturo Ortega (Neurotoxicity Research, 2020)

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

Genetic evaluation of domestication-related traits in rice: implications for the archaeobotany of rice origins - Ryo Ishikawa; Cristina C. Castillo; Dorian Q. Fuller (Archaeological and Anthropological Sciences, 2020)

Temporal and latitudinal comparisons of reproductive parameters in a heavily exploited shark, the bonnethead, Sphyrna tiburo (L. 1758), in the southern Gulf of Mexico - Daniela Palacios‐Hernández; José L. Castillo‐Géniz; Iván Méndez‐Loeza; Juan C. Pérez‐Jiménez (Journal of Fish Biology, 2020)
In the southern Gulf of Mexico, the bonnethead shark, Sphyrna tiburo , is one of the most frequently captured species in landings of small‐scale fisheries. Based on the analysis of two fishery‐dependent sampling periods (1993–1994 and 2007–2014), this study aimed to determine reproductive parameters and identify temporal differences between the two time periods. In the first sampling period, 776 males and 352 females with a size range of 28.0–120.0 cm total stretched length ( L T ) were analysed, and in the second sampling period, 387 males and 432 females with a size range of 28.0–122.0 cm L T were analysed. The size at 50% maturity in the second sampling period was significantly different between sexes, 82.6 cm L T for females and 73.8 cm L T for males (no estimation was possible for the first sampling period). The size at 50% maternity was not different between sampling periods, 97.3 cm L T for the first sampling period and 99.0 cm L T for the second sampling period. Litter size varied from 3 to 19 embryos and the average was not statistically different in both periods, 10.1 (S.D. = 3.8) for the first sampling period and 11.3 (S.D. = 3.5) for the second sampling period. The female reproductive cycle is asynchronous, and it seems to be annual, with a gestation period of 5–6 months, and a consecutive ovarian cycle and gestation period. Temporal (between sampling periods) and latitudinal (southern Gulf versus northern regions) variations occur in the synchronicity of the reproductive cycle, temporal variation in the relationship between maternal length and litter size, and latitudinal variation in average size of mature sharks.

White-Faced Capuchin, Cebus capucinus imitator, Hammerstone and Anvil Tool Use in Riparian Habitats on Coiba Island, Panama - Claudio M. Monteza-Moreno; Tamara Dogandžić; Kevin A. McLean; Pedro L. Castillo-Caballero; Zarluis Mijango-Ramos; Evelyn Del Rosario-Vargas; Margaret C. Crofoot; Brendan J. Barrett (International Journal of Primatology, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Combining Isotopic Techniques to Assess Historical Sediment Delivery in a Forest Catchment in Central Chile - C. Bravo-Linares; P. Schuller; A. Castillo; A. Salinas-Curinao; L. Ovando-Fuentealba; E. Muñoz-Arcos; A. Swales; M. Gibbs; G. Dercon (Journal of Soil Science and Plant Nutrition, 2020)

Transcriptomics, chromosome engineering and mapping identify a restorer-of-fertility region in the CMS wheat system msH1 - Cristina Rodríguez-Suárez; Paolo Bagnaresi; Luigi Cattivelli; Fernando Pistón; Almudena Castillo; Azahara C. Martín; Sergio G. Atienza; Carmen Ramírez; Antonio Martín (Theoretical and Applied Genetics, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Utilization of naproxen by Amycolatopsis sp. Poz 14 and detection of the enzymes involved in the degradation metabolic pathway - B. M. Alanis-Sánchez; S. M. Pérez-Tapia; S. Vázquez-Leyva; I. Mejía-Calvo; Z. Macías-Palacios; L. Vallejo-Castillo; C. M. Flores-Ortiz; C. Guerrero-Barajas; J. A. Cruz-Maya; J. Jan-Roblero (World Journal of Microbiology and Biotechnology, 2019)

Field Performance of Two Methods for Detection of Poliovirus in Wastewater Samples, Mexico 2016–2017 - Concepción F. Estívariz; Elda E. Pérez-Sánchez; Anita Bahena; Cara C. Burns; Howard E. Gary; Herlinda García-Lozano; Gloria Rey-Benito; Silvia Peñaranda; Katy V. Castillo-Montufar; Raúl S. Nava-Acosta; John Scott Meschke; M. Steven Oberste; et al. (Food and Environmental Virology, 2019)

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

The effects of commonly used anaesthetics on colour measurements across body regions in the poeciliid fish, Girardinus metallicus - Erin M. Wojan; Nalana C. Carreiro; David A. Clendenen; Heather M. Neldner; Crystal Castillo; Susan M. Bertram; Gita R. Kolluru (Journal of Fish Biology, 2019)
The effects of common anaesthetics on the hue, saturation and brightness measurements of the poeciliid fish Girardinus metallicus were investigated in two experiments. For both experiments the coloration of four body regions was measured from digital images of the same males obtained under three conditions: (1) control (in a water‐filled chamber); (2) anaesthetised with MS‐222; and (3) anaesthetised with eugenol (clove oil). In experiment 1 anaesthetised fish were photographed out of water. In experiment 2 all photographs were taken in a water‐filled chamber. Anaesthetics altered coloration in both experiments. In the more methodologically consistent experiment 2 we found significantly different hue, increased saturation and decreased brightness in anaesthetic v . control conditions, consistent with darkening caused by the anaesthetics. The body regions differed in coloration consistent with countershading but did not differentially change in response to anaesthesia. These findings suggest that photographing fish in a water‐filled chamber without anaesthetic is preferable for obtaining digital images for colour analysis and that multiple body regions of fish should be measured when assessing coloration patterns meaningful in behavioural contexts, to account for the gradients caused by countershading. We are encouraged that some researchers employ such methods already and caution against using anaesthetics except when absolutely necessary for immobilisation.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

Evaluation of chromatophores as natural marks for delta smelt: the effects of life-stage and light intensity - Gonzalo C. Castillo; Marade E. Sandford; Tien-Chieh Hung; Wan-Ru Yang; Galen Tigan; Luke Ellison; Joan C. Lindberg; Erwin E. Van Nieuwenhuyse (Environmental Biology of Fishes, 2019)

Transgenerational effects of inter-ploidy cross direction on reproduction and F2 seed development of Arabidopsis thaliana F1 hybrid triploids - Dorota Duszynska; Bjarni Vilhjalmsson; Rosa Castillo Bravo; Sandesh Swamidatta; Thomas E. Juenger; Mark T. A. Donoghue; Aurélie Comte; Magnus Nordborg; Timothy F. Sharbel; Galina Brychkova; Peter C. McKeown; Charles Spillane (Plant Reproduction, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pattern Recognition Applied to Attenuation of Multiples in Subsalt Imaging - J. C. Ortiz-Alemán; J. Abreu-Torres; M. G. Orozco-del-Castillo; J. J. Hernández-Gómez (Pure and Applied Geophysics, 2019)

The BeWo cell line derived from a human placental choriocarcinoma is permissive for respiratory syncytial virus infection - M. A. Velázquez-Cervantes; M. Martínez-Castillo; L. D. González-García; T. A. Vargas-Pavía; M. G. Martínez-Salazar; I. Mancilla-Herrera; G. León-Reyes; J. García-Cordero; A. C. Helguera-Repetto; M. León-Juárez (Virus Genes, 2019)

Return period curves for extreme 5-min rainfall amounts at the Barcelona urban network - X. Lana; M. C. Casas-Castillo; C. Serra; R. Rodríguez-Solà; A. Redaño; A. Burgueño; M. D. Martínez (Theoretical and Applied Climatology, 2019)

Apparent timing of density banding in the Caribbean coral Siderastrea siderea suggests complex role of key physiological variables - B. E. Benson; J. P. Rippe; C. B. Bove; K. D. Castillo (Coral Reefs, 2019)

Passalidae (Coleoptera: Scarabaeoidea) of the Biogeographical Province of Chocó and the West Andean Region of Colombia, with the Description of Two New Species - L Jiménez-Ferbans; P Reyes-Castillo; J C Schuster (Neotropical Entomology, 2018)

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

Rainfall intensity patterns derived from the urban network of Barcelona (NE Spain) - Xavier Lana; C. Serra; M. C. Casas-Castillo; R. Rodríguez-Solà; A. Redaño; A. Burgueño (Theoretical and Applied Climatology, 2018)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Ocean–atmosphere conditions related to severe and persistent droughts in the Mexican Altiplano - José Pablo Vega‐Camarena; Luis Brito‐Castillo; Luis M. Farfán; David J. Gochis; Luis F. Pineda‐Martínez; Sara C. Díaz (International Journal of Climatology, 2018)
Ocean and atmospheric patterns associated with the most severe and most persistent droughts in the Mexican Altiplano region are explored. The standardized precipitation index on a time scale of 12 months was used and compared with time series of other atmospheric conditions to identify major dry episodes from 1970 to 2012. The time series were derived from the second mode of a varimax‐rotated empirical orthogonal functional analysis from the mean summer rainfall series observed at weather stations located in the Mexican Altiplano from 1970 through 2000. The results showed that the longest and most persistent episode occurred from 1998 through 2001, while the most severe dry episode occurred in 2011–2012, when the Pacific Decadal Oscillation was in a negative phase and the Atlantic Multidecadal Oscillation in a positive phase, both in combination with a La Niña event. A large upper‐level anticyclone over the north‐central United States is related to droughts in the Altiplano. Under these conditions, the droughts were linked to a large anticyclone positioned over the central‐north of the United States, with consequent negative anomalies of specific humidity over central‐northern Mexico. Concurrent with droughts in the interior of Mexico, are positive rainfall anomalies along the central Pacific coast of Mexico near the study area. Under different atmospheric conditions, opposite anomalous behaviour between the coast and interior can exist. The mechanism driving this see‐saw behaviour between the west coast of Mexico and the Altiplano is explored.

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department - J. González del Castillo; A. Julian-Jiménez; F. González-Martínez; J. Álvarez-Manzanares; P. Piñera; C. Navarro-Bustos; M. Martinez-Ortiz de Zarate; F. Llopis-Roca; M. Debán Fernández; J. Gamazo-Del Rio; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Extracellular DNA and lipoteichoic acids interact with exopolysaccharides in the extracellular matrix of Streptococcus mutans biofilms - Midian C. Castillo Pedraza; Tatiana F. Novais; Roberta C. Faustoferri; Robert G. Quivey; Anton Terekhov; Bruce R. Hamaker; Marlise I. Klein (Biofouling, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Expression Changes in Metal-Resistance Genes in Microbacterium liquefaciens Under Nickel and Vanadium Exposure - Grisel Fierros-Romero; José A. Wrosek-Cabrera; Marlenne Gómez-Ramírez; Reynaldo C. Pless; A. M. Rivas-Castillo; Norma G. Rojas-Avelizapa (Current Microbiology, 2017)

Effects of feeding ground pods of Enterolobium cyclocarpum Jacq. Griseb on dry matter intake, rumen fermentation, and enteric methane production by Pelibuey sheep fed tropical grass - S. Albores-Moreno; J. A. Alayón-Gamboa; A. J. Ayala-Burgos; F. J. Solorio-Sánchez; C. F. Aguilar-Pérez; L. Olivera-Castillo; J. C. Ku-Vera (Tropical Animal Health and Production, 2017)

Variability among strains of Aspergillus section Nigri with capacity to degrade tannic acid isolated from extreme environments - F. Lara-Victoriano; F. Veana; F. D. Hernández-Castillo; C. N. Aguilar; M. H. Reyes-Valdés; R. Rodríguez-Herrera (Archives of Microbiology, 2017)

Assessment of a fisheries legal framework for potential development of an ecosystem approach to fisheries management in large rivers - T. I. Castillo; C. R. M. Baigún; P. G. Minotti (Fisheries Management and Ecology, 2016)
Most small‐scale fisheries of large floodplain rivers are still managed under conventional top‐down regulations that limit the application of an ecosystem approach to fisheries ( EAF ) due to inappropriate legal frameworks. Using the Parana–Paraguay River fisheries (Argentina) as an example, this study examines the extent to which existing provincial legislations can be prepared for the adoption of an EAF . An Ecosystem Fishing Legal Approach ( EFLA ) framework is proposed based on different criteria across an environmental–ecological, fishing, social, economic and institutional template. Policy Component Scores ( PCS ) and an Integrated Policy Legal Index ( IPLI ) were applied to assess the degree of compliance by current provincial legislations to EAF implementation. Cluster analysis was used to recognise the potential for articulating a legal framework at a basin scale. The EFLA framework, which provided an accurate picture of how provinces were poorly prepared to adopt an EAF for the Paraguay–Parana fisheries, and represents a suitable tool that can be adapted and extended to other basins around the world.

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Passipassalus brevicornis n. sp.: a New Passalidae (Coleoptera) from Brazilian Amazonian, with a Key to the Species of Passipassalus Reyes-Castillo & Fonseca - L Jiménez-Ferbans; P Reyes-Castillo; C R V da Fonseca (Neotropical Entomology, 2016)

Drivers of fluorescent dissolved organic matter in the global epipelagic ocean - T. S. Catalá; X. A. Álvarez‐Salgado; J. Otero; F. Iuculano; B. Companys; B. Horstkotte; C. Romera‐Castillo; M. Nieto‐Cid; M. Latasa; X. A. G. Morán; J. M. Gasol; C. Marrasé; et al. (Limnology and Oceanography, 2016)
Fluorescent dissolved organic matter (FDOM) in open surface waters ( 70%) than for the amino acid‐like components ( a . Positive non‐linear relationships between both predictor variables and the two humic‐like PARAFAC components suggest that their distribution are biologically controlled. Compared with the dark ocean (> 200 m), the relationships of C1 and C2 with AOU indicate a higher C1/AOU and C2/AOU ratios of the humic‐like substances in the dark ocean than in the surface ocean where a net effect of photobleaching is also detected. C3 (tryptophan‐like) and C4 (tyrosine‐like) variability was mostly dictated by salinity ( S ), by means of positive non‐linear relationships, suggesting a primary physical control of their distributions at the global surface ocean scale that could be related to the changing evaporation‐precipitation regime. Remarkably, bacterial biomass (BB) only contributed to explain a minor part of the variability of C1 and C4.

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state - H. M. González-Sánchez; A. Monsiváis-Urenda; C. A. Salazar-Aldrete; A. Hernández-Salinas; D. E. Noyola; M. E. Jiménez-Capdeville; A. Martínez-Serrano; C. G. Castillo (Journal of NeuroVirology, 2015)

Revision of Begomovirus taxonomy based on pairwise sequence comparisons - Judith K. Brown; F. Murilo Zerbini; Jesús Navas-Castillo; Enrique Moriones; Roberto Ramos-Sobrinho; José C. F. Silva; Elvira Fiallo-Olivé; Rob W. Briddon; Cecilia Hernández-Zepeda; Ali Idris; V. G. Malathi; Darren P. Martin; et al. (Archives of Virology, 2015)

Removal of heavy metals and arsenic from aqueous solution using textile wastes from denim industry - D. I. Mendoza-Castillo; C. K. Rojas-Mayorga; I. P. García-Martínez; M. A. Pérez-Cruz; V. Hernández-Montoya; A. Bonilla-Petriciolet; M. A. Montes-Morán (International Journal of Environmental Science and Technology, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Injury of the Developing Cerebellum: A Brief Review of the Effects of Endotoxin and Asphyxial Challenges in the Late Gestation Sheep Fetus - Lisa C. Hutton; Edwin Yan; Tamara Yawno; Margie Castillo-Melendez; Jon J. Hirst; David W. Walker (The Cerebellum, 2014)

Study of the vegetation in the Multiple Use Natural Reserve of Monterrico (Guatemala) - A. García-Fuentes; F.J. Castillo-Cabrera; C.V. Dávila-Pérez; A.S. Morales; C. Salazar-Mendías; M.L. Lendínez-Barriga; J.A. Torres-Cordero; L. Ruiz-Valenzuela (Plant Biosystems, 2014)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

Biodegradation of organic pollutants in saline wastewater by halophilic microorganisms: a review - Laura C. Castillo-Carvajal; José Luis Sanz-Martín; Blanca E. Barragán-Huerta (Environmental Science and Pollution Research, 2014)

Critical slowing down and noise-induced intermittency in bistable perception: bifurcation analysis - Alexander N. Pisarchik; Rider Jaimes-Reátegui; C. D. Alejandro Magallón-García; C. Obed Castillo-Morales (Biological Cybernetics, 2014)

Begomovirus diversity in tomato crops and weeds in Ecuador and the detection of a recombinant isolate of rhynchosia golden mosaic Yucatan virus infecting tomato - Lenin C. Paz-Carrasco; Gloria P. Castillo-Urquiza; Alison T. M. Lima; Cesar A. D. Xavier; Leticia M. Vivas-Vivas; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Regional signatures of plant response to drought and elevated temperature across a desert ecosystem - Seth M. Munson; Esteban H. Muldavin; Jayne Belnap; Debra P. C. Peters; John P. Anderson; M. Hildegard Reiser; Kirsten Gallo; Alicia Melgoza-Castillo; Jeffrey E. Herrick; Tim A. Christiansen (Ecology, 2013)
The performance of many desert plant species in North America may decline with the warmer and drier conditions predicted by climate change models, thereby accelerating land degradation and reducing ecosystem productivity. We paired repeat measurements of plant canopy cover with climate at multiple sites across the Chihuahuan Desert over the last century to determine which plant species and functional types may be the most sensitive to climate change. We found that the dominant perennial grass, Bouteloua eriopoda , and species richness had nonlinear responses to summer precipitation, decreasing more in dry summers than increasing with wet summers. Dominant shrub species responded differently to the seasonality of precipitation and drought, but winter precipitation best explained changes in the cover of woody vegetation in upland grasslands and may contribute to woody‐plant encroachment that is widespread throughout the southwestern United States and northern Mexico. Temperature explained additional variability of changes in cover of dominant and subdominant plant species. Using a novel empirically based approach we identified “climate pivot points” that were indicative of shifts from increasing to decreasing plant cover over a range of climatic conditions. Reductions in cover of annual and several perennial plant species, in addition to declines in species richness below the long‐term summer precipitation mean across plant communities, indicate a decrease in the productivity for all but the most drought‐tolerant perennial grasses and shrubs in the Chihuahuan Desert. Overall, our regional synthesis of long‐term data provides a robust foundation for forecasting future shifts in the composition and structure of plant assemblages in the largest North American warm desert.

Erratum to: Protected Graft Copolymer Excipient Leads to a Higher Acute Maximum Tolerated Dose and Extends Residence Time of Vasoactive Intestinal Peptide Significantly Better than Sterically Stabilized Micelles - Sandra Reichstetter; Gerardo M. Castillo; Israel Rubinstein; Akiko Nishimoto-Ashfield; ManShun Lai; Cynthia C. Jones; Aryamitra Banerjee; Alex Lyubimov; Duane C. Bloedow; Alexei Bogdanov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

Protected Graft Copolymer Excipient Leads to a Higher Acute Maximum Tolerated Dose and Extends Residence Time of Vasoactive Intestinal Peptide Significantly Better than Sterically Stabilized Micelles - Sandra Reichstetter; Gerardo M. Castillo; Israel Rubinstein; Akiko Nishimoto-Ashfield; ManShun Lai; Cynthia C. Jones; Aryamitra Banjeree; Alex Lyubimov; Duane C. Bloedow; Alexei Bogdanov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

Population structure, habitat features and genetic structure of managed red deer populations - J. Pérez-González; A. C. Frantz; J. Torres-Porras; L. Castillo; J. Carranza (European Journal of Wildlife Research, 2012)

Antibiotic therapy in necrotising external otitis: case series of 32 patients and review of the literature - C. Pulcini; P. Mahdyoun; E. Cua; I. Gahide; L. Castillo; N. Guevara (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Identification and origin of host-associated volatiles attractive to Prorops nasuta, a parasitoid of the coffee berry borer - Ariana K. Román-Ruíz; Edi A. Malo; Graciela Huerta; Alfredo Castillo; Juan F. Barrera; Julio C. Rojas (Arthropod-Plant Interactions, 2012)

Evaluation of four phenotypic methods to detect plasmid-mediated AmpC β-lactamases in clinical isolates - M. J. Gude; C. Seral; Y. Sáenz; M. González-Domínguez; C. Torres; F. J. Castillo (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evaluation of an immunochromatographic dip strip test for simultaneous detection of Cryptosporidium spp, Giardia duodenalis, and Entamoeba histolytica antigens in human faecal samples - P. Goñi; B. Martín; M. Villacampa; A. García; C. Seral; F. J. Castillo; A. Clavel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

E2F1 induces p19INK4d, a protein involved in the DNA damage response, following UV irradiation - Abel L. Carcagno; Luciana E. Giono; Mariela C. Marazita; Daniela S. Castillo; Nicolás Pregi; Eduardo T. Cánepa (Molecular and Cellular Biochemistry, 2012)

Size, shape and hue modulate attraction and landing responses of the braconid parasitoid Fopius arisanus to fruit odour-baited visual targets - Jeanneth Pérez; Julio C. Rojas; Pablo Montoya; Pablo Liedo; Francisco J. González; Alfredo Castillo (BioControl, 2012)

Development of wild barley (Hordeum chilense)-derived DArT markers and their use into genetic and physical mapping - C. Rodríguez-Suárez; M. J. Giménez; N. Gutiérrez; C. M. Ávila; A. Machado; E. Huttner; M. C. Ramírez; A. C. Martín; A. Castillo; A. Kilian; A. Martín; S. G. Atienza (Theoretical and Applied Genetics, 2012)

Detection and characterization of a ST6 clone of vanB2-Enterococcus faecalis from three different hospitals in Spain - M. López; A. Rezusta; C. Seral; C. Aspiroz; C. Marne; M. J. Aldea; I. Ferrer; M. J. Revillo; F. J. Castillo; C. Torres (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

High genetic variability and recombination in a begomovirus population infecting the ubiquitous weed Cleome affinis in northeastern Brazil - Sarah J. C. da Silva; Gloria P. Castillo-Urquiza; Braz T. Hora Júnior; Iraildes P. Assunção; Gaus S. A. Lima; Gilvan Pio-Ribeiro; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2011)

The Uptake of Copper by Aldama dentata: Ecophysiological Response, Its Modeling, and the Implication for Phytoremediation - N. Dasgupta-Schubert; M. G. Barrera; C. J. Alvarado; O. S. Castillo; E. M. Zaragoza; S. Alexander; S. Landsberger; S. Robinson (Water, Air, & Soil Pollution, 2011)

Three thousand years of flank and central vent eruptions of the San Salvador volcanic complex (El Salvador) and their effects on El Cambio archeological site: a review based on tephrostratigraphy - D. Ferrés; H. Delgado Granados; W. Hernández; C. Pullinger; H. Chávez; C. R. Castillo Taracena; C. Cañas-Dinarte (Bulletin of Volcanology, 2011)

A novel monopartite begomovirus infecting sweet potato in Brazil - Leonardo C. Albuquerque; Alice K. Inoue-Nagata; Bruna Pinheiro; Simone da G. Ribeiro; Renato O. Resende; Enrique Moriones; Jesús Navas-Castillo (Archives of Virology, 2011)

Four years of vertebrate monitoring on an upper Amazonian river - Nigel C. A. Pitman; Darren Norris; Jerry Martínez Gonzalez; Eriberto Torres; Fernando Pinto; Hernán Collado; Wilberth Concha; Raúl Thupa; Edwin Quispe; Jorge Pérez; Juan Carlos Flores del Castillo (Biodiversity and Conservation, 2011)

MHC class II DRB diversity in raccoons (Procyon lotor) reveals associations with raccoon rabies virus (Lyssavirus) - Vythegi Srithayakumar; Sarrah Castillo; Rick C. Rosatte; Christopher J. Kyle (Immunogenetics, 2011)

Molecular variability among isolates of Mycosphaerella graminicola, the causal agent of septoria tritici blotch, in Argentina - N. Castillo; C. Cordo; M. R. Simón (Phytoparasitica, 2010)

Females of a viviparous fish (Skiffia multipunctata) reject males with black colouration - A. Moyaho; P. Guevara-Fiore; E. Beristain-Castillo; C. Macías Garcia (Journal of Ethology, 2010)

Poly-β-Hydroxyalkanoate Exert a Protective Effect Against Carbon Starvation and Frozen Conditions in Sphingopyxis chilensis - P. Pavez; J. L. Castillo; C. González; Miguel Martínez (Current Microbiology, 2009)

Observed tendencies in maximum and minimum temperatures in Zacatecas, Mexico and possible causes - Luis Brito‐Castillo; Sara C. Díaz Castro; Raúl S. Ulloa Herrera (International Journal of Climatology, 2009)
At a global level, warming caused by the increase in greenhouse gases has been reported in different parts of the world. This warming resulted in a reduction in the diurnal temperature range (DTR), caused by a faster rate of increase in minimum temperatures. However, the tendency toward warming is not obvious in Zacatecas, Mexico. The tendencies in maximum and minimum temperatures are partly linked to the state of the low frequency variability of large‐scale atmospheric flow patterns, as depicted by the 700‐mb geopotential height anomalies. Analyses of maximum and minimum temperatures from 23 climate stations, from 1963 to 2002, show that the DTR in southern Zacatecas is increasing from a rise in maximum temperatures and drop in minimum temperatures, while the DTR in northern Zacatecas is decreasing from a faster rate of decline in maximum temperatures than the increase in minimum temperatures. The regional series related to the F1 and F2 leading modes, after applying a Varimax‐rotated empirical orthogonal function analysis to the 23 DTR series, acceptably reproduce the north–south dipole of DTR changes, while the point‐correlation analysis between the two regional series, the 700‐mb geopotential height anomalies and the indices of Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation indicate that the DTR in Zacatecas, Mexico is related to fluctuations in subtropical and extratropical circulations. Copyright © 2008 Royal Meteorological Society

Enhanced duckweed detection using bootstrapped SVM classification on medium resolution RGB MODIS imagery - C. Castillo; I. Chollett; E. Klein (International Journal of Remote Sensing, 2008)

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs - S. Carrillo; E. López; M. M. Casas; E. Avila; R. M. Castillo; M. E. Carranco; C. Calvo; F. Pérez-Gil (Journal of Applied Phycology, 2008)

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Arrarás (Immunogenetics, 2008)

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Ararrás (Immunogenetics, 2008)

Correlation between the presence of symptoms and the Giardia duodenalis genotype - J. Sahagún; A. Clavel; P. Goñi; C. Seral; M. T. Llorente; F. J. Castillo; S. Capilla; A. Arias; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Exogenous Abscisic Acid Increases Carbohydrate Accumulation and Redistribution to the Grains in Wheat Grown Under Field Conditions of Soil Water Restriction - Claudia Travaglia; Ana C. Cohen; Herminda Reinoso; Carlos Castillo; Rubén Bottini (Journal of Plant Growth Regulation, 2007)

Digestive responses of two omnivorous rodents (Peromyscus maniculatus and P. alstoni) feeding on epigeous fungus (Russula occidentalis) - T. D’Alva; C. Lara; A. Estrada-Torres; C. Castillo-Guevara (Journal of Comparative Physiology B, 2007)

Plasma Zinc Concentration, Body Composition and Physical Activity in Obese Preschool Children - G. Weisstaub; E. Hertrampf; D. López de Romaña; G. Salazar; C. Bugueño; C. Castillo-Duran (Biological Trace Element Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cinnamtannin B-1 from bay wood exhibits antiapoptotic effects in human platelets - A. Bouaziz; C. Romera-Castillo; S. Salido; P. J. Linares-Palomino; J. Altarejos; A. Bartegi; J. A. Rosado; G. M. Salido (Apoptosis, 2007)

Prevalence of fecal carriage of ESBL-producing Enterobacteriaceae in hospitalized and ambulatory patients during two non-outbreak periods - F. J. Castillo García; C. Seral García; M. P. Gandara; M. I. Millán Lou; C. Pitart Ferré (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

ORIGINAL ARTICLE: Elevational parallels of latitudinal variation in the proportion of lianas in woody floras - M. Jiménez‐Castillo; S. K. Wiser; C. H. Lusk (Journal of Biogeography, 2007)
Aim To determine if elevational variation in the proportion of lianas in woody floras parallels the variation observed on latitudinal gradients. This is to be expected if the poleward decrease in the importance of lianas is related to the vulnerability of their wide vessels to freeze embolism. Location Coastal ranges of south‐central Chile (latitude 37°–40° S) and western South Island of New Zealand (41°–43° S). Methods The presence of all woody species was recorded in plots of 2500 m 2 (Chile) or 100–400 m 2 (New Zealand) on four elevational gradients in temperate rain forest. Each species was classified as a tree, shrub or liana. Original data were obtained from 22 plots at two sites in Chile. In New Zealand, two surveys comprising a total of 296 plots were extracted from the National Vegetation Survey data base. Results Liana species richness declined more or less monotonically on all four gradients, whereas richness of trees and shrubs showed more varied elevational patterns. The proportion of woody species contributed by the liana life‐form was negatively correlated with elevation on all four gradients, falling from 15 to 35% of the woody flora at c . 200 m a.s.l. to nil well below the tree line. The elevational and latitudinal limits of liana species were marginally significantly correlated in Chile, but not in New Zealand. Main conclusions The elevational parallel of the well‐documented decline in liana representation with increasing latitude is consistent with the hypothesis that cold intolerance is a strong control on the global distribution of the liana life‐form.

Influence of Grain Processing on Acid–Base Balance in Feedlot Steers - C. Castillo; J. Hernández; J. Méndez; J. Llena; V. Pereira; M. López-Alonso; J. L. Benedito (Veterinary Research Communications, 2006)

Early effects of tillage and crop rotation on arbuscular mycorrhizal fungal propagules in an Ultisol - C. G. Castillo; R. Rubio; J. L. Rouanet; F. Borie (Biology and Fertility of Soils, 2006)

Mitochondrial Genome Dynamics in Plants and Animals: Convergent Gene Fusions of a MutS Homologue - Ricardo V. Abdelnoor; Alan C. Christensen; Saleem Mohammed; Bryan Munoz-Castillo; Hideaki Moriyama; Sally A. Mackenzie (Journal of Molecular Evolution, 2006)

Interactions Between Nitrate Assimilation and 2,4-Dinitrophenol Cometabolism in Rhodobacter capsulatus E1F1 - V.M. Luque-Almagro; R. Blasco; L. Paloma Sáez; M. D. Roldán; C. Moreno-Vivián; F. Castillo; M. Martínez-Luque (Current Microbiology, 2006)

Climatic cycles inferred from the aminostratigraphy and aminochronology of Quaternary dunes and palaeosols from the eastern islands of the Canary Archipelago - J. E. Ortiz; T. Torres; Y. Yanes; C. Castillo; J. De La Nuez; M. Ibáñez; M. R. Alonso (Journal of Quaternary Science, 2006)
Aminochronological and aminostratigraphical methods have been used to study the Quaternary aeolian deposits from the islands located east of the Canary Archipelago (Fuerteventura and Lanzarote islands and La Graciosa, Montaña Clara and Alegranza islets). The extent of racemisation/epimerisation of four amino acids (isoleucine, aspartic acid, phenylalanine and glutamic acid) was measured in land snail shells of the genus Theba . The age calculation algorithms of these amino acids have been determined to permit the numerical dating of these deposits. Eight Aminozones, each defining dune/palaeosol‐formation episodes, have been distinguished and dated at 48.6 ± 6.4, 42.5 ± 6.0, 37.8 ± 4.6, 29.4 ± 4.8, 22.4 ± 4.5, 14.9 ± 3.6, 11.0 ± 4.0 and 5.4 ± 1.1 ka BP, the first five of them defining cycles of 5–7 ka. The alternation of palaeosols and aeolian deposits, which are related to abrupt transitions from humid to arid conditions, are the reflection of globally induced changes in North Africa palaeoenvironmental conditions linked to the effect of African palaeomonsoons on the trade winds and the Saharan Air Layer. Probably these aeolian cycles, with a recurrence period of 5–7 ka, are the expression of multiples of the ∼2.4 ka solar‐cycle. Copyright © 2005 John Wiley & Sons, Ltd.

Factors Affecting Fertility According to the Postpartum Period in Crossbred Dual-Purpose Suckling Cows in the Tropics - F. Perea-Ganchou; E. Soto Belloso; C. González Stagnaro; G. Soto Castillo; H. Hernández Fonseca (Tropical Animal Health and Production, 2005)

18th International Mouse Genome Conference - Amy C. Lossie; Thomas P. Meehan; Andrew Castillo; Lihua Zheng; Keith C. Weiser; Mark A. Strivens; Monica J. Justice (Mammalian Genome, 2005)

Effects of ovariectomy and growth hormone administration on body composition and vascular function and structure in old female rats - C. Castillo; M. Cruzado C. Ariznavarreta; V. Lahera; V. Cachofeiro; P. Gil-Loyzaga; Jess A. F. Tresguerres (Biogerontology, 2005)

Cryptic isolation of Gulf of California shovelnose guitarfish evidenced by mitochondrial DNA - J. Sandoval-Castillo; A. Rocha-Olivares; C. Villavicencio-Garayzar; E. Balart (Marine Biology, 2004)

Cell wall composition and structure of Yarrowia lipolytica transposon mutants affected in calcofluor sensitivity - José Ruiz-Herrera; Patricia García-Maceira; Luis C. Castillo-Barahona; Eulogio Valentín; Rafael Sentandreu (Antonie van Leeuwenhoek, 2003)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Genetic loci associated with field resistance to late blight in offspring of Solanum phureja and S.tuberosum grown under short-day conditions - M. Ghislain; B. Trognitz; Ma. del R. Herrera; J. Solis; G. Casallo; C. Vásquez; O. Hurtado; R. Castillo; L. Portal; M. Orrillo (Theoretical and Applied Genetics, 2001)

Phylogenetic analysis of dengue-3 viruses prevalent in Guatemala during 1996-1998 - S. Usuku; L. Castillo; C. Sugimoto; Y. Noguchi; Y. Yogo; N. Kobayashi (Archives of Virology, 2001)

Temporal occurrence of Ceratium hirundinella in Spanish reservoirs - C. Pérez-Martínez; P. Sánchez-Castillo (Hydrobiologia, 2001)

Some properties of semicarbazide-sensitive amine oxidase (SSAO) from human cerebrovascular tissues - C. Smeraldi; V. Castillo; J. M. Lizcano; M. Unzeta (Inflammation Research, 2001)

Polymorphism of the 5′ terminal region of Citrus tristeza virus (CTV) RNA: Incidence of three sequence types in isolates of different origin and pathogenicity - M. A. Ayllón; C. López; J. Navas-Castillo; S. M. Garnsey; J. Guerri; R. Flores; P. Moreno (Archives of Virology, 2001)

Causes and consequences of salt-marsh erosion in an Atlantic estuary in SW Spain - J. M. Castillo; C. J. Luque; E. M. Castellanos; M. E. Figueroa (Journal of Coastal Conservation, 2000)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Use of a Selective Medium and a Membrane Filter Method for Isolation of Campylobacter Species from Spanish Paediatric Patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Use of a selective medium and a membrane filter method for isolation ofCampylobacter species from Spanish paediatric patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Fusarium and Fumonisins in Corn at Harvest Time: Effect of Fertilization and Planting Area - M. L. Ramirez; A. Torres; M. Rodriguez; C. Castillo; S. Chulze (Cereal Research Communications, 1997)

A preliminary study of the behaviour and vitality of reseeded juvenile great scallops, of three sizes in three seasons - P. G. Fleury; C. Mingant; A. Castillo (Aquaculture International, 1996)

Regulation of reduced nitrogen assimilation in Rhodobacter capsulatus E1F1 - Francisco Javier Caballero; Isabel Igeo; Jacobo Crdenas; Francisco Castillo (Archives of Microbiology, 1989)

Ammonia assimilation pathways in Rhodopseudomonas capsulata E1F1 - C. Moreno-Vivin; F. J. Cejudo; J. Crdenas; F. Castillo (Archives of Microbiology, 1983)